Intrathoracic Kidney after Blunt Abdominal Trauma: A Case Report and Review of the Literature - Fikret Halis; Akin Soner Amasyali; Aysel Yucak; Turan Yildiz; Ahmet Gokce (Case Reports in Urology)
Abdominal trauma is responsible for most genitourinary injuries. The incidence of renal artery injury and intrathoracic kidney is quite low in patients who present with blunt trauma experiencing damage. There are four defined etiologies for intrathoracic kidney, which include real intrathoracic ectopic kidney, eventration of the diaphragm, congenital diaphragmatic herniation, and traumatic diaphragmatic rupture. The traumatic intrathoracic kidney is an extremely rare case. We presented intrathoracic kidney case after traumatic posterior diaphragmatic rupture.